The Effects of Different Re-Warm-Up Strategies on Power, Changing of Direction and Ball Shooting Velocity in Well-Trained Soccer Players - Demetris Matsentides; Marios Christou; Nikolaos Zaras (Sports, 2023)
The purpose of the study was to investigate whether a re-warm-up training session either with tuck jumps and linear sprints or with changing of directions may enhance power, agility or ball shooting velocity in well-trained soccer players. Ten soccer players (age: 18.2 ± 1.7 years; body mass: 64.4 ± 8.0 kg; body height: 1.71 ± 0.04 m) participated in the study. Players performed three different re-warm-up interventions including no re-warm-up (C), change of direction (COD) and jump-sprint condition (JS). Before each re-warm-up intervention, players performed the same warm-up condition followed by 8 min of passive rest. Following the re-warm-up interventions, countermovement jump (CMJ), T-Test agility time-trial and ball shooting velocity were measured. Performance in CMJ height, power and power per body mass remained unchanged following all three conditions (p > 0.05). However, the agility time-trial was significantly reduced following COD re-warm-up compared to C (−1.7 ± 1.6%, p = 0.03). Ball shooting velocity was increased following COD compared to C (4.7 ± 3.8%, p = 0.014), while a statistical trend was found between JS and C interventions (4.8 ± 5.4%, p = 0.060). These results suggest that a re-warm-up intervention including changing of directions may significantly enhance T-Test agility time-trial and ball shooting velocity in well-trained soccer players.